Social media, freedom of speech, and the future of our democracy - edited by Lee C. (New York Oxford University Press, 2022)
One of the most fiercely debated issues of the current era is what to do about 'bad' speech on the internet, primarily speech on social media platforms such as Facebook and Twitter. 'Bad' speech encompasses a range of problematic communications--hate speech, disinformation and propaganda campaigns, encouragement of and incitement to violence, limited exposure to ideas one disagrees with or that compete with preexisting beliefs, and so on. ... [T]he premise of the current debate is that the ubiquity and structure of this newest and most powerful communications technology magnifies these harms exponentially beyond anything we have encountered before. Some argue that, if it is left unchecked, the very existence of democracy is at risk
Includes bibliographical references (pages 331-392) and index.
Keywords: Freedom of speech--United States